PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT SISTEM PENGUKURAN KINERJA SISTEM PENGHARGAAN MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL (Studi Empiris Pada Perhotelan Di Pekanbaru) - Rosfariana Marbun; Vince Ratnawati; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research was to analyze the effect of total quality management, performance measurement system, system of rewards, motivation and organizational commitment to managerial performance partially or simultaneously. This research was conducted in the hospitality pekanbaru by respondents as many as 150 managers. Data collected through a survey using questionnaires. Questionnaires distributed directly to the manager any hospitality at pekanbaru 150 questionnaires. Spreading was done on August 20, 2016 until August 23, 2016. The questionnaire back as much 79.Metode statistics used to test the hypothesis in this research is multiple linear regression. The result of this study indicate that the total quality management system, performance measurement systems, reward systems and motivation had a significant effect on managerial performance. However to the organization's commitment doesn’t have significant effect on the managerial performance. there are still many limitatios and short comings the effect of independent variables on the dependent variable can only explain by 81%, hence more independent variable are needed. Based on these results, further research are expected to use more independent variables such as leadership style, balanced scorecard, organizational culture and others.Keywords : Management, Performence, Motivation and Commitment